Teacher's Perception of the Principal's Leadership - Inom Nasution; Amiruddin Siahaan; Ismail Ismail; Sugeng Sukoco (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study answers the question of how teachers perceive the leadership of the madrasa principal. The type of this research is a qualitative approach with a descriptive-analytical study method, towards Madrasah Aliyah Negeri 1 Tapanuli Tengah. The focus of the research analysis includes aspects of behavior, experience, and leadership strategies of the madrasa principal. The results of this study indicate that (1) the leadership behavior displayed by the madrasa principal is perceived as good by the teachers. This is indicated by the exemplary figure displayed by the head of the madrasa and in line with the needs of the teacher, although there are still weaknesses in the aspect of providing learning facilities in madrasas. (2) the experience provided by the head of the madrasa, namely creating a conducive learning climate, appreciating the performance of educators, and providing creative and innovative space for teachers in education. (3) the leadership strategy practiced by the head of the madrasa to the teacher provides support (motivation) to the implementation of professional practice in education, including the provision of guidance, direction, and teaching practice through teacher delegations to participate in education and training (training), Subject Teacher Deliberation activities (MGMP), as well as reminding teachers about optimizing daily and monthly performance in the momentum of monthly apples in madrasas.